The Role of Trade Openness and Macroeconomic Factors in Shaping FDI Inflows to Vietnam - Quang, Phung Duy; Huyen, Nguyen Khanh; Linh, Pham Thi My; Minh, Nguyen Nhat (Southeast Asia Development Research, 2025)
Purpose - This study explores the linkages between trade and investment flows in the Vietnamese economy, analyzing how these dynamics influence economic growth and stability. By examining the impact of trade and investment, the study aims to identify ways to optimize Vietnam’s economic policies to promote sustainable development. Design/ Methodology/ Approach - Using a Vector Autoregressive (VAR) model, this study explores the causal relationship between trade, foreign direct investment (FDI) and macroeconomic indicators. Secondary data on trade openness, FDI inflows, GDP and other macroeconomic indicators from official sources are used to estimate the short-run and long-run effects on Vietnam’s economic linkages. Findings - The study analyzed the impact of trade openness on foreign direct investment (FDI) flows during the period 1997-2022 using a VAR model, showing that trade openness has a negative impact on FDI in the short term but a positive impact in the long term. In addition, the study also provides important policy implications, supporting the government in planning and adjusting more effective economic management strategies. Originality/Value - This study contributes to the limited literature on Vietnam’s economic linkages, especially in the context of VAR model application. It provides an in-depth understanding of the relationship between trade and investment and offers valuable recommendations for policy makers in enhancing Vietnam’s economic resilience and growth through adjusting trade and investment strategies.